The disaster-causing factors of the flash floods for the July 20th extreme rainstorm in Henan, China - He, Bingshun; Li, Changzhi; Yao, Qiuling; Wang, Han; Luo, Lanyang; Ma, Meihong (Frontiers in Earth Science, 2024)
Global warming has accelerated the frequency and intensity of extreme rainfall events in mountainous areas. Coupled with their vulnerable environment and the impact of intensive human activities, along with the complex and variable causes of flash floods, this exacerbates casualties and property losses.Therefore, this article investigates the triggering mechanisms and potential disaster-causing factors of the extreme "720" flood in the WZD-HGZ basin of Henan. The research results indicate that the flash floods in the WZD-HGZ basin were primarily caused by prolonged heavy rainfall, combined with the complex terrain, obstructive backwater, and human activities. The amplification of the flood mainly occurred in three stages: concentrated runoff from multiple channels, water obstruction caused by the successive collapse of roadbeds and bridges, and the generation of backwater. Besides, due to the lack of basic flood prevention awareness, unclear warnings, and inadequate guidance, the transition chain from issuing warnings to taking action was disrupted. The aforementioned research findings provide references for current flash flood disaster prevention efforts.